Memoryless variable structure control for affine nonlinear systems using only output information. (27th October 2014) - Yan, Xing‐Gang; Spurgeon, Sarah K.; Zhu, Quanmin; Zhang, Qingling
Summary: In this paper, local stabilisation is considered for a class of affine nonlinear control systems with uncertainties involving time‐varying delay. It is not assumed that either the dimension of the inputs is equal to the dimension of the outputs or that the nominal system is linearisable or partially linearisable. The bounds on both the matched and mismatched uncertainties are nonlinear and time delayed. A static output feedback variable structure control is synthesized to stabilise the system uniformly asymptotically. A control strategy to enforce exponential stability is also derived. The Lyapunov–Razumikhin approach is used to deal with the effect of the time delay, and the bounds on the uncertainties are used in the control design to enhance the robustness. The designed control does not depend on the time delay, and thus, it is not required that the time delay is known. Finally, the obtained results are tested on a simple mechanical system through simulation. The simulation results show that the proposed approach is effective and feasible. Copyright © 2014 John Wiley & Sons, Ltd.